Gas cylinders. Design, construction and testing of refillable composite gas cylinders and tubes. Fully wrapped fibre reinforced composite gas cylinders and tubes up to 450 l with load-sharing metal liners Part 2, (27th November 2020) - British Standards Institution,
No abstract available